Celiac disease - a pluripathological model in pediatric practice - Lupu, Vasile Valeriu; Sasaran, Maria Oana; Jechel, Elena; Starcea, Iuliana Magdalena; Ioniuc, Ileana; Mocanu, Adriana; Rosu, Solange Tamara; Munteanu, Valentin; Nedelcu, Alin Horatiu; Danielescu, Ciprian; Salaru, Delia Lidia; Knieling, Anton; et al. (Frontiers in Immunology, 2024)
Being defined as an autoimmune, chronic pathology, frequently encountered in any age group, but especially in pediatrics, celiac disease (also called gluten enteropathy), is gaining more and more ground in terms of diagnosis, but also interest in research. The data from the literature of the last decades attest the chameleonic way of its presentation, there may be both classic onset symptoms and atypical symptoms. Given the impact played by celiac disease, especially in the optimal growth and development of children, the current narrative review aims to highlight the atypical presentation methods, intended to guide the clinician towards the inclusion of the pathology in the differential diagnosis scheme. To these we add the summary presentation of the general data and therapeutic lines regarding the underlying condition and the existing comorbidities. In order to place the related information up to date, we performed a literature review of the recent articles published in international databases.We bring forward the current theories and approaches regarding both classic celiac disease and its atypical manifestations. Among these we note mainly constitutional, skin or mucous, bone, neuro-psychic, renal, reproductive injuries, but also disorders of biological constants and association with multiple autoimmunities. Knowing and correlating them with celiac disease is the key to optimal management of patients, thus reducing the subsequent burden of the disease.